Carbon-silicon species are unlikely in subduction-zone fluids - Nanfei Cheng; I-Ming Chou; Ying Chen; Zhenhao Duan; Xiaolin Wang; Hao Yan (Communications Earth & Environment)
Abstract In subduction zones, carbon-bearing fluids play a pivotal role in deep carbon cycling and global climate change. Given that Earth’s interior is dominated by silicates, the existence of aqueous carbon-silicon (C-Si) species is crucial for assessing the magnitude of return flux of carbon from subducting slabs to mantle wedges and ultimately Earth’s surface, yet it remains controversial. To resolve this controversy, we undertake a comprehensive in situ investigation of high pressure–temperature fluids employing optical cells and Raman spectroscopy under conditions comparable to those of previous studies. Under oxidizing conditions near the C-CO2 buffer, our findings show no evidence for C-Si species. Notably, under reducing conditions, a shoulder peak near the dominant CH4 peak, previously interpreted as evidence for C-Si speciation, emerges in high-temperature CH4-bearing fluids without silicates and even in pure CH4, suggesting it simply comes from CH4 hot bands. Therefore, C-Si species are unlikely in subduction-zone fluids.